'Yummy or crummy?' The multisensory components of medicines-taking among HIV-positive youth. Issue 2 (1st February 2019) - Hodes, Rebecca; Vale, Beth; Toska, Elona; Cluver, Lucie; Dowse, Ros; Ashorn, Mikael
ABSTRACT: The global rollout of Antiretroviral Treatment (ART) has revealed an urgent need to understand the medicines-taking practices of HIV-positive adolescents. In the last decade, the literature on the social determinants of health has broadened the evidence-base on ART adherence. Interdisciplinary studies have expanded conceptions of medicines-taking beyond clinical or health systems frameworks, recognising the importance of socio-structural conditions and of patients' beliefs and experiences. Participatory research techniques which foreground the perspectives of adolescents provide greater insights still into their adherence. This article explores the use of participatory methods within a broader study on the social determinants of ART adherence among HIV-positive adolescents in South Africa. We describe how participatory methods were incorporated into this study ( n = 1, 059 in the quantitative baseline). We focus on an exercise, 'Yummy or crummy?', that explored the multisensory dimensions of medicines-taking, including their colour, smell, shape, and delivery mechanism. We describe two principal findings: first, adolescents' preference for greater understanding of the chemical workings of medicines, manifested in their preferences for colour, taste and shape of medicines; and second, the vital relationship between sensory preferences and the social imperatives of discretion and confidentiality regarding HIV-status.